Influence of different thermal degradation processes on the optical property of Pyromark-2500. (15th March 2023) - Martínez, N.; Lopez-Herraiz, M.; Rico, A.; Múnez, C.J.; Poza, P.
Highlights: Absorber coating degradation depending on the heating and cooling rate. Optical properties degradation when the coating is removed. Mismatch effect and substrate oxidation promote degradation. To use mix rule to estimate the surface absorptance. Abstract: Concentrating solar power (CSP) is emerging as an increasingly important component of renewable energy. CSP systems are being widely adopted in the establishment of large-scale thermal power plants, with an increase in the number of successfully operating demonstration systems. Special coatings are generally used in various types of receivers for solar collector systems. Selective coatings are used for receivers intended to be operated at low or medium temperatures. Similar selective coatings are not currently available for application under high temperatures. In such cases, high-temperature absorbing coatings are generally used to improve the thermal efficiency of the receiver and protect their tubes from oxidation. It is worthwhile to observe the behaviour of such coatings when exposed to high fluxes for extended periods, in order to develop more efficient technologies. Currently, the essential properties for characterizing the paint are absorptivity, emissivity, and structural integrity of the coating (adhesion and cohesion). Good understanding of the behaviour of this paint under representative operating conditions would help to improve the design of the plant, maintain its performance and maintain the thermal efficiency of the receiver. The principal objective of this study was to provide extensive knowledge of the durability and variation of the optical properties of Pyromark when it is consolidated with improved methods. No degradation or loss of optical performance was observed at temperatures under 700 °C. The substrate affected the crystalline structure of an initial coating at high temperatures owing to the diffusion of metal ions. Concentrated solar radiation was the main factor that affected the integrity of the coating. At concentrations higher than 550× suns, a significant area of the irradiated samples was found to be uncoated. These results can be used to design more accurate latest generation receivers to improve the performance of this technology.